François Dorval-Langlois de Fancan, Georges de Scudéry et le débat sur l’appartenance générique du roman - Pawłowska, Maja (Romanica Silesiana)
Le Tombeau des romans (1626), attributed to Fancan, discusses the usefulness of romances and historiography. In the first part of his pamphlet, Fancan criticizes fiction’s artifice as a lie. In the second part, however, the writer praises fiction as a way of teaching the truth in a veiled manner. Ibrahim (1641) appeared with a preface attributed to Georges de Scudéry, in which the questions of literary rules, probability (vraisemblance) and historicity in romances are asked. Writings on the novel of Fancan and Scudéry comprise important French treatises of the 17th century, which show the evolution of the genre of romance. Key words: French 17th century romance, François Dorval-Langlois de Fancan, Georges de Scudéry.